Pengaruh Penambahan EM4 dan Ekstrak Daun Lamtoro (Leucena leucocephala) terhadap Pupuk Organik Cair Limbah Cair Tahu (C-Karbon dan N-Nitrogen) - Mualim; Febby; Aplina Kartika Sari (Poltekkes Kemenkes Bengkulu, 2025)
Tofu industrial liquid waste will affect water bodies if it is disposed of directly without prior management, causing problems with water quality and other biota. This research aims to determine the difference in improving the quality of CCarbon and N-Nitrogen with the addition of EM4 and lamtoro leaves. The research method uses quasi-experiment. Based on the results of the average levels of C-Carbon and N-Nitrogen produced from liquid organic fertilizer with 1 Kg treatment; 1.5 Kg; 2 Kg and control results from the one way anova test obtained a p-value for C-Carbon levels of 0.198 ≥ 0.05, which means that statistically there is no significant difference, while the results of the one way anova test for N levels obtained a p-value of 0.033 ≤ 0.05, which means there is a significant difference. It can be concluded from the results of this study that C-Carbon levels do not have a significant difference while N-Nitrogen has a significant difference. It is hoped that the community can use tofu liquid waste as an alternative to liquid organic fertilizer in controlling environmental pollution.